Понятійний апарат дослідження державного регулювання розвитку освітньої системи - Zastrozhnokova , Iryna (Theory and Practice of Public Administration, 2019)
The state regulation of the educational system of Ukraine begins with the consolidation of the rights of citizens to education in the constitution of Ukraine. In the context of the formation of a full and detailed conceptual apparatus of state regulation of the development of the educational sphere, it is expedient to provide definition and research of the essence of the following concepts: "state regulation", "state administration", "educational activity" and "educational system". The educational system is a concept that reflects the inalienable component of any society or community and includes the field of preschool, extracurricular, general secondary, vocational, higher and postgraduate education, self-education, postgraduate studies and doctoral studies. In society, there is a need for the preparation and adaptation of their citizens to life in society and the world around them, and the educational system itself is responsible for this process. The concept of state regulation should be determined on the basis of the general theory of management, taking into account the particular sphere of activity of state bodies, which are of executive character. Consequently, "state regulation" is a broader concept than "public administration", since it covers the broader scope of state activity. Therefore, state regulation is closely linked to the forms of public administration. The main body of executive power in the field of education and science is the Ministry of Education and Science of Ukraine (MES), whose activities are guided by the Cabinet of Ministers of Ukraine. The main missions of the ministry are to ensure the development and implementation of state policy in the following areas: education and science, scientific, scientific and technical and innovation activities, technology transfer. State regulation of education is a system of social, political, organizational, legal, and economic methods and forms of influence on subjects of educational processes that determine the environment for the realization of tasks and goals that can simultaneously meet both the strategic interests of the state and the immediate interests of themselves these subjects.